2013
DOI: 10.1159/000353119
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Molecular Identification of Four Uncommon Alpha Globin Variants in Thailand

Abstract: Alpha thalassemia is the most common genetic disease in the world with the prevalence of carriers ranging from 5-50% in several populations. Coinheritance of two defective α-globin genes usually gives rise to a symptomatic condition, hemoglobin (Hb) H disease. Previously, it has been suggested from several studies in different populations that nondeletional Hb H disease (--/αTα or --/ααT) is generally more severe than the deletional type (--/-α). In this report, we describe four rare nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…In addition, non-deletional α-thalassemia is not rare. α WS α, which is rather rare in other parts of the world 32 , is the most prevalent non-deletion type of α-thalassemia, with a gene frequency of 0.26%. Several studies on different populations have suggested that the non-deletion types of Hb H disease(--/α T α) are usually more severe than the deletion types (--/-α), with greater anaemia, jaundice, splenomegaly and early anaemic symptoms, and a higher proportion of patients who require blood transfusion and splenectomy 28, 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, non-deletional α-thalassemia is not rare. α WS α, which is rather rare in other parts of the world 32 , is the most prevalent non-deletion type of α-thalassemia, with a gene frequency of 0.26%. Several studies on different populations have suggested that the non-deletion types of Hb H disease(--/α T α) are usually more severe than the deletion types (--/-α), with greater anaemia, jaundice, splenomegaly and early anaemic symptoms, and a higher proportion of patients who require blood transfusion and splenectomy 28, 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical signs of DENV infection reflect the different levels of severity including dengue fever or dengue hemorrhagic fever, or dengue shock syndrome (DSS). Patients with more severe forms of the disease display hemorrhagic disorders, including plasma leakage, thrombocytopenia, hemoconcentration, and multi-organ failure [ 1 6 ]. Liver transaminase (alanine transaminase [ALT] and aspartate transaminase [AST]) levels increase in both DENV-infected patients [ 7 10 ] and murine models of DENV infection [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported in Thai population. 16 Our patient may be one of those cases who carries this rare mutation. In our study, comparison of clinical spectrum and severity between patients with Hb H disease and AE Bart’s disease was evaluated.…”
Section: Discussionmentioning
confidence: 81%